Revisiting the origin of non-volatile resistive switching in MoS2 atomristor - Asif A. Shah; Aadil Bashir Dar; Mayank Shrivastava (npj 2D Materials and Applications)
Abstract Recently, Non-Volatile Resistive Switching (NVRS) has been demonstrated in Metal-monolayer MoS2-Metal atomristors. While experiments based on Au metal report the origin of NVRS to be extrinsic, caused by the Au atom adsorption into sulfur vacancies, however, more recently molecular dynamics based on reactive forcefield (ReaxFF) suggest that both monolayer and multilayer MoS2 can also host intrinsic non-volatile resistive states whereby an S atom at a monosulfur vacancy (parent state) pops into the molybdenum plane (popped state) under applied out-of-plane electric field. Our rigorous computations based on Density Functional Theory (DFT) and M3GNet (deep learned forcefield) to carry out structural relaxations and molecular dynamics reveal that such a popped state is unstable and does not represent any intrinsic non-volatile resistive state. This is in contrast with the ReaxFF used in previous studies which inaccurately describes the Potential Energy Surface (PES) of MoS2 around the popped state. More importantly, Au atom adsorbed at a sulfur vacancy in MoS2 atomristors represents a stable non-volatile resistive state which is in excellent agreement with earlier experiment. Furthermore, it is observed that the local heating generated around the adsorbed Au atom in low resistive state leads to cycle-to-cycle variability in MoS2 atomristors.